Rectum dose constraints for carbon ion therapy: relative biological effectiveness model dependence in relation to clinical outcomes - Choi, Kyungdon; Mairani, Andrea (Cancers, 2020)
The clinical application of different relative biological effectiveness (RBE) models for carbon ion RBE-weighted dose calculation hinders a global consensus in defining normal tissue constraints. This work aims to update the local effect model (LEM)-based constraints for the rectum using microdosimetric kinetic model (mMKM)-defined values, relying on RBE translation and the analysis of long-term clinical outcomes. LEM-optimized plans of treated patients, having suffered from prostate adenocarcinoma (n = 22) and sacral chordoma (n = 41), were recalculated with the mMKM using an in-house developed tool. The relation between rectum dose-volume points in the two RBE systems (DLEM|v and DMKM|v) was fitted to translate new LEM-based constraints. Normal tissue complication probability (NTCP) values, predicting late rectal toxicity, were obtained by applying published parameters. No late rectal toxicity events were reported within the patient cohort. The rectal toxicity outcome was confirmed using dosimetric analysis: DMKMVHs lay largely below original constraints; the translated DLEM|v values were 4.5%, 8.3%, 18.5%, and 35.4% higher than the nominal DMKM|v of the rectum volume, v—1%, 5%, 10% and 20%. The average NTCP value ranged from 5% for the prostate adenocarcinoma, to 0% for the sacral chordoma group. The redefined constraints, to be confirmed prospectively with clinical data, are DLEM|5cc ≤ 61 Gy(RBE) and DLEM|1cc ≤ 66 Gy(RBE).